Propriedades eletrônicas e estruturais de nanotubos híbridos BxCyNz - Anjos, Jansen Felix dos (2022)
In this work, we perform an ab-initio study of the structural stability and electronic structure of BxCyNz nanotubes using Density Functional Theory based calculations implemented in SIESTA. Namely, we aim to investigate hybrid nanotubes electronic and structural properties and how their chirality and diameter influence such properties. Two island configurations were used, the first island with one BN ring and the second with seven BN rings. The analysis of the formation energy as a function of diameter showed similar behavior for both zigzag and armchair structures having a decay with increasing diameter, which has the function aD2, where D is the diameter of the tube. It was also analyzed that with the increase of the island, the formation energy increases, making the structures on the second island less stable. In the strain energy, a decay that follows the law of 1/D2 concerning diameter was found, where this energy for zigzag nanotubes is slightly lower than armchair nanotubes. This may be because armchair structures have fewer bonds parallel to diameter growth and fewer C − C bonds. We found that the presence of the BN rings can interfere with the electronic properties since some metallic nanotubes became semiconductors for the structures on the first island, except for the nanotube (6,0), but with the second island, all nanotubes became semiconductors.